2008
DOI: 10.1002/med.20127
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐tethered proteins for basic research, imaging, and therapy

Abstract: Secreted and intracellular proteins including antibodies, cytokines, major histocompatibility complex molecules, antigens, and enzymes can be redirected to and anchored on the surface of mammalian cells to reveal novel functions and properties such as reducing systemic toxicity, altering the in vivo distribution of drugs and extending the range of useful drugs, creating novel, specific signaling receptors and reshaping protein immunogenicity. The present review highlights progress in designing vectors to targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 182 publications
0
20
0
Order By: Relevance
“…20 A more selective approach to activate glucuronide prodrugs is to anchor bG on the membrane of tumor cells. 21,22 We have previously found that tumor-located expression of membrane-tethered bG greatly sensitized tumor cells to a glucuronide produg of p-hydroxyaniline mustard and produced strong antitumor activity in vivo. 23 In a recent study, we demonstrated that stable expression of a membrane-tethered form of bG on EJ bladder cancer cells increased their sensitivity to SN-38G and enhanced the therapeutic efficacy of CPT-11 in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…20 A more selective approach to activate glucuronide prodrugs is to anchor bG on the membrane of tumor cells. 21,22 We have previously found that tumor-located expression of membrane-tethered bG greatly sensitized tumor cells to a glucuronide produg of p-hydroxyaniline mustard and produced strong antitumor activity in vivo. 23 In a recent study, we demonstrated that stable expression of a membrane-tethered form of bG on EJ bladder cancer cells increased their sensitivity to SN-38G and enhanced the therapeutic efficacy of CPT-11 in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, humanization of the anti-PEG reporter did not hamper its activity; the humanized anti-PEG reporter displayed high imaging specificity in subcutaneous and metastatic tumor models in vivo as determined by smallanimal PET and optical imaging. A wide range of transmembrane domains derived from human proteins including the human B7-1 antigen have been used to anchor heterologous proteins on cells (9), which will facilitate complete humanization of the human anti-PEG reporter. The human anti-PEG reporter, the first example of a humanized antibody used as a reporter gene, may provide a powerful tool for monitoring the efficacy of gene or cell therapy and survival of organ transplants in humans by multiple imaging systems.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane-anchored antibodies are attractive for the development of highly specific and nonimmunogenic reporter genes (9)(10)(11)(12). Antibody reporters can be designed to exhibit low immunogenicity by using antibodies derived from the species of interest.…”
mentioning
confidence: 99%
“…8). In this study, we expressed a membrane-tethered anti-CD3 antibody (CD3L) on poorly immunogenic melanoma cells to activate CD3 + lymphocytes locally in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In this strategy, antibodies with specificity for activation receptors present on lymphocytes are expressed on the surface of cancer cells by fusing the antibody to a transmembrane domain or glycosylphosphatidylinositol anchor (8). We and others have shown that membrane-tethered antibodies with specificity for CD3 or the T-cell receptor can potently trigger activation of naBve T cells and significantly suppress tumor growth in mice (9 -12).…”
mentioning
confidence: 99%